The impact of typical neovascular age-related macular degeneration and polypoidal choroidal vasculopathy on vision-related quality of life in Asian patients. Issue 5 (2nd August 2016) - Fenwick, Eva K; Cheung, Chui Ming Gemmy; Ong, Peng Guan; Tan, Gavin; Lee, Shu Yen; Yeo, Ian; Cheng, Ching Yu; Wong, Tien Y; Lamoureux, Ecosse L
Abstract : Aims: To determine the impact of neovascular age-related macular degeneration (nAMD) on vision-related quality of life (VRQoL) in an Asian population. Methods: In this cross-sectional study, 162 subjects with nAMD from the Asian AMD Phenotyping Study and 105 randomly sampled age-matched and gender-matched controls from the population-based Singapore Chinese Eye Study were recruited. nAMD was categorised as either polypoidal choroidal vasculopathy (PCV) or 'typical' AMD (tAMD). The reading, mobility and emotional well-being subscales of the impact of vision impairment (IVI) scale were validated using Rasch analysis and used as the main outcome measures and collectively referred to as VRQoL. Multivariate linear regression analyses were performed to assess the impact of nAMD overall, and PCV and tAMD subtypes, on the three IVI domains. Results: Of the 162 with nAMD, 103 (63.6%) had PCV and 59 (36.4%) had tAMD. In multivariate models, nAMD overall was independently associated with a 21% reduction in reading (β=−1.08; CI −1.58 to −0.57); 16% reduction in mobility (β=−0.74; −1.14 to −0.33) and 44% reduction in emotional well-being (β=−2.15; −2.83 to −1.47) compared with controls. There were significant VRQoL deficits (p<0.05) associated with both PCV and tAMD; these deficits were similar and not statistically different between the two nAMD subtypes (p>0.05). Conclusions: Neovascular AMD, including both PCV and tAMD subtypes, has a detrimental impact on VRQoL in Asian subjects independent of level of vision impairment. Interventions to increase reading capacity, enhance mobility and independence and improve mental health outcomes for subjects with neovascular AMD further address the impact of the condition on VRQoL in addition to pharmacological therapies.